Design, fabricate and test composite space components - Cheung, Jun Jie (2010)
This report covers the progress of the author in fulfilling his final year project. The project is about the design and analysis of composite reflector petals of a deployable parabolic antenna, as part of a collaboration project between Defence Science and Technology Agency (DSTA) and Nanyang Technological University (NTU). After some studies, the author came up with proposed design changes to the petals’ thickness and base support, and recommended suitable composite materials for use in fabricating them, in which one of them was studied and used as a basis for the design and analysis. Structural analysis using Finite Element Method (FEM) was carried out to understand the performance of the petals in operation; the fields that were covered in the analysis are the natural frequencies of the composite petals, the mechanical stress and strain built up in the petals during the launch phase, and thermally induced expansion and contraction of the petals in the orbit phase. Recommendations for the design is then made based from the analysis.